2018
DOI: 10.1038/s41598-018-35129-5
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Susceptibility to a Neonicotinoid Insecticide after Fetal and Early Postnatal Exposure

Abstract: Neonicotinoids have become the most widely used class of insecticides world-wide. Although numerous studies have documented neonicotinoid toxicity in bees and other insects, the effects of exposure during early development in mammals remain largely unexplored. We assessed the effects of the neonicotinoid imidacloprid (IMI) in adult male and female mice after in utero and early postnatal exposure. Pregnant mice were infused with IMI (0.5 mg/kg/day) from gestational day 4 to the end of nursing at postnatal day 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…In general, they show a high potency on insect receptors, while they have been designed for low affinities on mammalian receptors (Tomizawa et al 2000 ; Tomizawa and Casida 2003 , 2005 ; Casida 2018 ). In regulatory studies, they have been proven to be relatively well-tolerated by rats, but some studies indicate an impact of neonicotinoids on mammals (Abou-Donia et al 2008 ; Duzguner and Erdogan 2012 ; Gibbons et al 2015 ; Burke et al 2018 ; Berheim et al 2019 ; Thompson et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, they show a high potency on insect receptors, while they have been designed for low affinities on mammalian receptors (Tomizawa et al 2000 ; Tomizawa and Casida 2003 , 2005 ; Casida 2018 ). In regulatory studies, they have been proven to be relatively well-tolerated by rats, but some studies indicate an impact of neonicotinoids on mammals (Abou-Donia et al 2008 ; Duzguner and Erdogan 2012 ; Gibbons et al 2015 ; Burke et al 2018 ; Berheim et al 2019 ; Thompson et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies have revealed multiple toxicity of neonicotinoids at a low dose, including neurotoxicity of imidacloprid at 0.77 mg/L [23], immunotoxicity of clothianidin at 0.1 mg/L [24], endocrine toxicity of imidacloprid at 0.03 mg/L and thiacloprid at 0.08 mg/L [25], and genotoxicity caused by oxidative stress [26]. A few in vivo studies have shown neurodevelopmental toxicity in rodents by imidacloprid 0.5 mg/kg/day, and acetamiprid 1 mg/kg/day, and neurotoxicity with clothianidin 10 mg/kg/day [2729]. These levels are the same or lower than the no-observed-adverse-effect levels (NOAELs) of 5.7 mg/kg/day for imidacloprid, 7.1 mg/kg/day for acetamiprid, and 9.7 mg/kg/day for clothianidin [30–32].…”
Section: Introductionmentioning
confidence: 99%
“…Fetuses are vulnerable to chemicals, and there is concern about the effect of prenatal exposure on the health of future generations. In fact, developmental exposure to NNs induces abnormalities in behavior [ 4 , 31 , 36 ] and delayed sexual maturation [ 32 ] in mice. However, there are currently few animal research models for elucidating the role of prenatal and perinatal exposure to NNs in the development of diseases in adult females.…”
mentioning
confidence: 99%